Development of a simple method based on LIBS for evaluation of neutron production targets made of hydrogen isotopes. (June 2021) - Gaviola, P.A.; Sallese, M.; Suarez Anzorena, M.; Ararat Ibarguen, C.E.; Bertolo, A.A.; Iribarren, M.; Perez, R.; Morel, E.; Torga, J.; Kreiner, A.J.; del Grosso, M.F.
Abstract: In the present work we propose a fast and simple method, based on Laser Induced Breakdown Spectroscopy (LIBS), to evaluate Neutron Production Targets. Targets of interest consist of hydrogen (particularly deuterium or tritium) contained in a titanium matrix. The method aims to evaluate the relative content of hydrogen within the titanium matrix, in order to determine if the target is "accepted" or "rejected" according to this content. Several deuterium targets have been fabricated (TiD x ), with different deuterium concentrations, and different techniques have been used to characterize their surfaces. Optical Coherent Tomography has been used to characterize the size and shape of LIBS holes, in order to determine LIBS depth of analysis. Grazing Incidence X-ray Diffraction has been used to determine a range for deuterium relative content. Elastic Recoil Detection Analysis (ERDA) is proposed for future LIBS calibration, since it provides a single value for relative content, has a depth of analysis similar to LIBS and also allows to distinguish between different isotopes. ERDA first results are reported in comparison with LIBS results. Highlights: Surface characterization of Neutron Production Targets. LIBS technique is proposed to evaluate deuterium content of NPT. Optical Coherent Tomography has been used to characterize LIBS holes. The combination of ERDA and LIBS techniques is a good option for NPT.